2017
DOI: 10.1177/2151458517692651
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3 Different Perioperative Care Models for Patients With Hip Fractures Within 1 Health Service

Abstract: Introduction:Orthogeriatric care models have been introduced within many health-care facilities to improve outcomes for hip fracture patients. This study aims to evaluate differences in care between 3 models, an orthopedic model, a geriatric model, and a comanaged model.Materials and Methods:A retrospective analysis was conducted for hip fracture patients treated at Western Health between November 2012 and March 2014. All patients aged 65 years or older were included in the analysis.Results:There were 183 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…The presentations section of the event was customized and attended by 20 to 50 team members (orthopedic ward, physicians from the orthopedic, anesthesia, and geriatric departments). Topics selected by a majority of departments were principles of comanaged care (7), preoperative optimization (7), and management of delirium (4). Other topics included were antibiotics, pain, and osteoporosis (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presentations section of the event was customized and attended by 20 to 50 team members (orthopedic ward, physicians from the orthopedic, anesthesia, and geriatric departments). Topics selected by a majority of departments were principles of comanaged care (7), preoperative optimization (7), and management of delirium (4). Other topics included were antibiotics, pain, and osteoporosis (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Orthogeriatric co-management improves the outcome of older adults with a fragility fracture and is the gold standard for care with proven outcomes and many published consensus guidelines. 1 - 7 Implementation of a geriatric fracture program has been reported in many settings and various barriers reported. 8 , 9 Successful implementation requires strong physician leadership to articulate both a short- and long-term plan, good communication to implement standardized plans of care working with all members of the healthcare team and to foster relationships both within the hospital and with other institutions in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the changes did not significantly impact mortality or complication rates during the hospital stay or after a 3-month follow-up. While detecting medical problems and preventing complications is one of the main tasks of the geriatrician in an orthogeriatric setting, Coventry et al [30] showed higher complication rates after involvement of a geriatrician. This increase is explained by a better detection of complications.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have demonstrated decreased length of in‐hospital stays, and thereby decreased costs, in addition to improvements in the functional results with collaborative models. However, those improvements have not been demonstrated in other comparative works. In any case, there seems to be a certain consensus, also in Spain, that collaborative care offers specific advantages to clinical care compared to other models.…”
Section: Introductionmentioning
confidence: 93%